Knowledge, Attitude, and Perception of Postmortem Examination Among Doctors and Nurses in a Tertiary Hospital of Sokoto, Nigeria - A U Kaoje; U Mohammed; A Abdulkarim; M O Raji; U M Ango; B A Magaji (Wolters Kluwer Medknow Publications, 2016)
Postmortem examination is a highly specialized surgical procedure that consists of a thorough examination of a corpse to determine the cause and manner of death and to evaluate any disease or injury that may be present. This study aimed to assess the knowledge, attitude, and perception of postmortem examination among doctors and nurses in a tertiary health care of Sokoto state. A cross-sectional study design was used, and a total of 149 doctors and nurses participated in the study. Respondents were recruited into the study using probability proportionate to size followed by a simple random sampling method. Data were obtained through self-administered questionnaires, and the data were analyzed using Statistical Package for Social Sciences Version 17.0. Descriptive statistics, Chi-square test, and multinomial logistic regression analysis were carried out. The mean age of respondents was 31.6 (5.6) years. There were more nurses than doctors (60.4% vs. 39.6%) in the study. More than three-quarter (80%) of the respondents had fair to good knowledge of postmortem examination. While many respondents expressed positive attitudes and perceptions, less than half were willing to accept organs from deceased donors. Respondents' profession influenced both the knowledge (P > 0.001, odds ratio [OR] = 13.95) and attitude (P < 0.04, OR = 2.49) to postmortem examination. Although greater than three-quarter of respondents had fair to good knowledge and many expressed positive attitudes and perceptions with respect to postmortem examination, there is need to create more awareness on medical benefit of postmortem examination.